Survival Response of Consortium Isolates from Diesel Contaminated Soil within Katsina State, Nigeria - Zubairu Darma, Umar; Musa, Aminu; Riko Yunusa, Yahaya (International Journal of Environment, 2020)
Environmental increase in the spilled diesel creates serious damages to our natural ecosystems. Biodegradation provide the best removal alternative for such diesel contamination. This study was carried out to monitor the bacteria survival response during diesel oil biodegradation. Bacteria isolation was carried out using plating technique and screened at varying diesel concentrations (0 to 10%, v/v) before being identified using the 16S rRNA gene sequencing. Bacteria consortia were formulated using the screened isolates through mathematical permutation approach. Prepared bacteria resting cells of the selected consortium was grown at 2%, v/v diesel oil which was co-contaminated with varying concentrations of Mg++, Mn++, Zn+, Co++ and Fe++ (0 to 4 g/L) in mineral salts medium. Total of 47 different bacteria strains were isolated and the finally screened isolates were identified as Alcaligenes sp., Ochrobactrum sp., Alcaligenes aquatilis and Alcaligenes faecalis UMYU001 (MN519483.1). These bacteria were found to be compatible with one another despite being obtained from different environments. Of the prepared consortia, combination 11 (CST11) was found to produce the highest population of 1.6 x 104 cfu/mL after 48 hours at 2% v/v diesel oil. This CST11 survived optimally at 35°C, 7.0, and 2% v/v of the temperature, pH and diesel oil respectively. Also, the resistance thresholds of the metals for CST11 include Mg++ (3.5 g/L) while Mn++, Zn++, Co++ and Fe++ were only resisted at 1 g/L. This recommends the consortium as good enough in surviving at the sole expense of diesel oil even in the presence of heavy metals co-contaminants.